A new Genus of Proctotrupidae from Japan (Hymenoptera: Proctotrupoidea). - Masner, Lubomir (Contributions to Entomology = Beiträge zur Entomologie, 1958)
The author has established a new genus - Watanabeia n. g. (Proctotrupidae) - for Disogmus afissae Watanabe, originally described from Japan. A short discussion concerning phylogenetic evaluation of the new genus is added. Finally a key to genera of Proctotrupidae of the world with their synonymy is given. Nomenclatural Acts Watanabeia Masner, 1958 (Proctotrupoidea), gen. n.